Utilizing Food Waste for Sustainable Packaging: A Biodegradable Approach to Replacing Plastic (International Journal of Smart Agriculture, 2025)
Plastic is harmful to human health and is not an environmentally friendly product. Over thousands of years, plastic does not degrade or decompose. Food waste has been used for years to replace plastic or plastic derivatives or create eco-friendly biodegradable packaging material. Packaging is vital for product protection and has a high value at all stages. Different materials have been introduced to replace plastic. This article discussed the use of various food waste to replace specific plastic packaging materials. A commonly accepted strategy for building a sustainable society is to use waste biomass such as fiber, cellulose, and starch to substitute petrochemical ingredients in manufacturing plastics. Bioplastics or biodegradable polymers are plastics manufactured from biomass. Mushroom waste has been used to make an alternative to Styrofoam, Mushroom pulp or fiber utilization for the development of Kraft paper packaging has shown to be the best alternative, as it has high mechanical strength, and it is biodegradable, organic, or non-hazardous to humans. Similarly, cucumber peel was used to make biodegradable packaging films that act as an oxygen barrier in the atmosphere. Cucumber peels can be employed as Nano-fillers in bio-composite film, resulting in effective food packaging materials with low ionic conductivity. Sugar cane bagasse is also an excellent alternative to plastic film packaging. Since agricultural wastes may be turned into new value-added commodities, sugarcane bagasse waste could contribute to societal economic success while fostering a green environment. Garlic peels are also being used to create paper packaging. Garlic peel-based biodegradable packs were evaluated and confirmed to be suitable for usage as carry bags or pouches. Foams, Kraft sheets, and Biofilms are used to protect fruits and vegetables, as well as beans, cereal, grains, and other food goods. However, these food waste materials can be used to produce biodegradable packaging material as an alternative to hazardous plastic.